Leveraging Telemedicine to Spread Expertise in Neonatal Resuscitation - Joaquim M. B. Pinheiro (MDPI AG, 2022)
The development and potential applications of telemedicine in neonatal resuscitation were reviewed by Donohue and colleagues in 2019, in a manuscript that compiled seminal references in the field [...]